The Existence of Notary Cooperation with Online Service Bureaus in the Making of Deeds of Establishment of Limited Liability Companies - Clarissa Chrysilla; Reinard Yudhaprawira (Lex Prospicit, 2023)
Notaries are authorized to mold all actions, agreements, and determinations desired by the parties who come to them to confirm them and pour into an authentic deed, aiming for the deed to have complete evidential power and validity. Therefore, notaries are obliged to fulfill all the provisions of their positions and other regulations and are responsible for the deeds they have prepared. In practice, especially since Covid-19 there are still notaries who cooperate with online service bureaus. The type of study is empirical juridical, which in other words is a type of sociological legal research, also known as field research, which examines the applicable legal provisions and what happens in reality in the community. From the research results obtained from decision No.36/PID.SUS/TPK/2014/PN.JKT.PST in conjunction with Cassation Court Decision No. 980 K/Pid.Sus/2015, that a notary does not check documents (the ID Card) in the creation of a company, and they aren’t to meet directly before the Notary, but with a service bureau. In this case, it is related to the validity of the company establishment deed that has been made by a notary in collaboration with an online service bureau, where the appearer does not appear before the notary because the one who appears before the notary is the service bureau. One of the main advantages of notary cooperation with online service bureaus is of course that it is not bound by working time. That the cooperation between the notaries does not have a written work bond but only in the form of verbal, however, such actions still violate the UUJN and the Notary Code of Ethics, and there have been lacunae in the law to regulate cooperation between notary and online service bureau. In the case that the author raises, notary cooperation with service bureaus is prone to criminal acts (corruption or fraud), therefore the company's deed of establishment becomes null and void. Second, the responsibility of the Notary Professional Organization, towards the Notary who cooperates with the online service bureau, which violates the provisions of the UUJN and the Code of Ethics, then based on Article 4 number 4 of the Notary Code of Ethics, it is said that the act of cooperating with an online service bureau is categorized as a violation of the notary code of ethics, which is accompanied by sanctions in the form of: Reprimand; Warning; Temporary dismissal from Association membership; Honorable dismissal from Association membership; and Dishonorable dismissal from Association membership. The INI's responsibility as a notary professional organization is as a form of providing duties and authority in providing guidance, supervision and protection to notaries.